The Character of Law and Authority in Medieval Bosnia - Behmen, Goran (Pregled: časopis za društvena pitanja / Periodical for social issues, 2010)
Understanding law and authority in Medieval Europe has been deeply influenced by religion. In that sense, authority of the time was theocratic. Such situation also prevailed in the Medieval Bosnian state. Many documents and first-rate historical sources serve as testimony to the understanding of authority and law. They are a formalized expression of understanding of the authority and law, which, in the period of Middle Ages in Bosnia, were based on the Christian vision of the world, as well as on religious subordination of the vassal to his senior. That can be seen in the example of intitulation of the Bosnian medieval diplomas and charters, both in Cyrillic and Latin alphabet, as well as in formal characteristics of the documents in the period of Middle Ages.